THE IMPACT OF IMPLEMENTING CIRCULAR ECONOMY PRACTICES ON WASTE MANAGEMENT IN UGANDA - Believein Kyatuhaire (Uganda Christian University, 2024)
The study majorly focused on the impact of Circular economy practices and waste management among firms in Uganda. The study was also guided alongside the following research objectives; examine the effect of reverse logistics practices on waste management, assess the effect of recycling on waste management and finally assess the relationship between circular economy and waste management in Uganda. The study also adopted a cross-sectional survey with a combination of qualitative-quantitative data collection methods for this study. A case research design will also be utilized, as this method allows for an in-depth examination of the specific context. Findings of the study on effect of reverse logistics practices on waste management revealed that majority of respondents agreed to the statements used to measure reverse logistics although some were not sure and others disagreed respectively. Furthermore, findings on effect of recycling on waste management revealed that majority of respondents also agreed to the statements used to measure recycling and waste management although some were not sure and others disagreed respectively. Finally, findings on relationship between circular economy practiced revealed positive significant relationship between reverse logistics, recycling and waste management. The study recommended that; manufacturing firms should adopt circular economy practices fully, enhancing Plastic Circularity using Technology, Revise Waste Management Policies, there is need to re-introduce incentives for plastic recycling, and finally the study also recommends that there is need to transition to a circular economy needs application of technologies that support the whole plastic value chain. The study concluded that indeed circular economy practices need to be adopted by manufacturing firms because of the varied advantages and the need to maximise waste management.